PENGARUH INDEPENDENSI AUDITOR INTERNAL DAN PROFESIONALISME TERHADAP EFEKTIVITAS STUKTUR PENGENDALIAN INTERNAL PADA PT PERTANI (PERSERO) CABANG SURAKARTA - Dhesy Andriarti, Dewi Saptantinah Puji Astuti & Fadjar Harimurti (Universitas Slamet Riyadi, 2017)
The purpose of this research is to analyze the significance of the influence ofinternal auditor independence and professionalism of the effectiveness of internalcontrol structures partially or simultaneously. The population in this study were allemployees of PT Pertani (Persero) Branch of Surakarta. Data obtained fromquestionnaires. The research concludes that (1) the t test results count of 2,105 witha probability value 0.045 < 0.05, which means the independence of the internalauditor positive and significant impact on the effectiveness of the internal controlstructure. (2) Results of the t test of 2,307 with a probability value 0,029 < 0,05,which means professionalism positive and significant impact on the effectiveness ofthe internal control structure. (3) The test results F count equal to 6,872 with p value0,004 < 0,05, which means the internal auditor independence and professionalismpositive and significant impact on the effectiveness of internal control structuressimultaneously.Keywords: internal control structure, effectiveness, independence, internal auditors,professionalism.